The Wage System Practices of Rubber Tappers in the Study of Sharia Economic Law - HAK, Nurmala; Jannah, Miftahul (Universitas Islam Negeri Raden Fatah Palembang, 2023)
Every transaction should be conducted in writing to avoid disputes in the future. However, many still engage in verbal transactions based on trust and honesty, as seen in the wage system for rubber tappers in Betung Village. The main focus of this research is to examine the implementation of the wage system for rubber tappers in Betung II Village. The research objective is to assess the wage system for rubber tappers in Betung II Village from the perspective of Sharia Economic Law. The research methodology used is field research, conducted directly in the field, specifically in Betung II Village, Lubuk Keliat District, Ogan Ilir Regency. The research utilizes qualitative data with both primary and secondary sources. Data collection techniques include observation, interviews, and documentation. Data is analyzed using qualitative descriptive techniques. The findings reveal that the wage system for rubber tappers in Betung II Village is divided into two methods: a flat-rate system and a percentage system. Both systems begin with verbal agreements between the landowner and the rubber tapper, without witnesses. To date, no disputes have arisen among the parties. In Sharia Economic Law, this system fulfills the pillars and conditions of ijarah. The determination of wages also aligns with the principles of feasibility and virtue, except for the principle of justice. In the context of Sharia Economic Law, this study falls under istihsan bi al-urf, meaning istihsan based on customary practices.